PENGARUH KUALITAS LAYANAN DAN FITUR APLIKASI MOBILE BANKING DIGI TERHADAP KEPUASAN NASABAH DI BANK BJB KCP KATAPANG - Oktapia, Tri; Ucu Supriatna (JCI Publisher, 2025)
Service quality and the use of DIGI mobile banking application features are factors that can influence customer satisfaction in utilizing digital banking services. This study aims to determine the effect of service quality and the use of DIGI mobile banking features on customer satisfaction at Bank BJB KCP Katapang. The research method employed was quantitative, with data collected through questionnaires distributed to 96 respondents, both via Google Form and printed sheets. Data processing was carried out using SPSS version 25. The analysis results show that service quality has a significant effect on customer satisfaction, with a significance value of 0.000 < 0.05 and a t-count of 3.839 > t-table of 1.986. Similarly, the DIGI mobile banking application features also have a significant effect, with a significance value of 0.000 < 0.05 and a t-count of 3.741 > t-table of 1.986. Simultaneously, service quality and application features have a positive and significant effect on customer satisfaction, as evidenced by a significance value of 0.000 < 0.05 and an F-count of 41.054 > F-table of 3.09. These findings highlight the importance of improving service quality and optimizing application features to maintain and enhance customer satisfaction.